AB0396 DIAGNOSTIC PROTOCOL INCLUDING MINIMALLY INVASIVE MINOR SALIVARY GLANDS BIOPSY IN SJÖGREN'S SYNDROME IN A SPANISH REFERENCE CENTER. (2nd June 2020) - Álvarez Troncoso, J.; Oñoro López, C. M.; Soto Abánades, C.; Ruiz Bravo, E.; Ramos Ruperto, L.; Blasco Santana, L.; Sorriguieta Torre, R.; Robles Marhuenda, Á.; Martínez Robles, E.; Noblejas Mozo, A.; Rios, J. J.; Arnalich Fernández, F.
Abstract : Background: Sjögren's syndrome (SjS) is a systemic autoimmune disease with a broad clinical presentation from dry syndrome to systemic extraglandular manifestations. The diagnosis can be complex since none of the markers, except anti-Ro, is sufficiently sensitive or specific. Although, minor salivary glands biopsy (MSGB), Schirmer's test and unstimulated whole salivary flows (UWSF) are the hallmark for the diagnosis of this entity, its use is not widespread in some centers. Objectives: The aim of the study was to analyze the usefulness and safety of the diagnostic protocol for the classification of SjS and the immunological and analytical markers in dry syndrome due to SjS. Methods: Prospective observational study of a cohort of patients with sicca syndrome from a reference center. The diagnostic protocol (Schirmer's test, UWSF and minimally invasive MSGB) was applied in the same consultation. Demographic, clinical, analytical and histological data were reviewed. Results: Over a period of 6 months, 48 patients with dry syndrome were analyzed, of which 39 women (81.2%). The main suspicion was SjS (39), followed by sarcoidosis (3), IgG4-related disease (2) and other diagnoses (4). The mean age was 59.1±4.4 years. Almost half (45.8%) reported xerostomia and 41.6% xerophthalmia. Recurrent parotidomegaly was described in 6 patients (12.5%) and arthralgias in 12 (25%). Immunologically, 23 (47.9%) presented anti-nuclear antibodies, 13 (27.1%) anti-Ro, 4 (8.3%) anti-La, 12 (25%) rheumatoid factor and 15 (31.2%) low C4. Schirmer test was positive in 32 patients (66.7%), UWSF in 22 (45.8%) and 9 (18.8%) had a focus score ≥1, although 16 (33.3%) had focal lymphocytic sialadenitis in the MSGB. A total of 21 (43, 8%) patients were classified according to the 2016 ACR/EULAR criteria. 12 (57.1%) were seropositive SjS and 9 (42.9%) seronegative SjS. MSGB sensitivity was 71% and specificity 96%. Patient reported symptoms were unhelpful to differentiate SjS from other causes of dry syndrome. The number of protocols needed to diagnose a SjS was 2.28 (5.33 in seronegative SjS). Complications associated with the procedure were low (1 of 48) and mild (self-limited paraesthesia). Patients with SjS, unlike those with dry syndrome of another etiology, had more anemia (p<0.001), lymphopenia (p=0.022), ESR (p=0.030), beta-2 microglobulin (p=0.011), ANA (p<0.001), anti-ENA (p=0.006), anti-Ro (p<0.001), low C4 (p<0.001) and hypergammaglobulinemia (p=0.002). Conclusion: Immunological and histological manifestations were more predictive than clinical ones to differentiate SjS from other causes of dry syndrome. MSGB is a simple, sensitive, specific and safe procedure. The application of the diagnostic protocol (Schirmer test, UWSF and MSGB) allowed to standardize the classification of SjS and increased the diagnosis of patients with seronegative SjS. References: [1]Ramos-Casals M, Brito-Zerón P, Bombardieri S On behalf of the EULAR-Sjögren Syndrome Task Force Group, et al . EULAR recommendations for the management of Sjögren's syndrome with topical and systemic therapies. Annals of the Rheumatic Diseases 2020;79: 3-18. [2]Guellec D, Cornec D, Jousse-Joulin S, et al. Diagnostic value of labial minor salivary gland biopsy for Sjögren's syndrome: a systematic review. Autoimmun Rev . 2013;12(3):416–420. Disclosure of Interests: None declared